Using targeted visceroception to improve interoceptive sensibility and emotion regulation. (January 2023) - Davey, Steven; Bell, Elliot; Halberstadt, Jamin
Abstract: Focusing on one's body can improve the awareness and regulation of emotion. Interoception – sensing the physiological condition of the body, particularly of the viscera – appears to play an important role. While the majority of previous research studies have examined interoceptive sensitivity (i.e., detection of objectively measurable physiological changes), there has been relatively limited investigation of interoceptive sensibility (i.e., subjective awareness of those changes), and even fewer studies permitting causal conclusions. The current study is part of a randomised controlled trial on visceroception in the context of emotion regulation, using an 8-week intervention involving focused attention on either cardiac or gastrointestinal activity. Group differences in emotion regulation and reactivity were assessed using the Multidimensional Assessment of Interoceptive Awareness (MAIA), the Difficulties in Emotion Regulation Scale, and the Emotion Reactivity Scale ( ERS ). The findings suggest that focussed attention on gastrointestinal activity (i.e., gastroception), in particular, improves interoceptive sensibility and emotion regulation, as evidenced by increases on the MAIA's Noticing, Body Listening, and Self-regulation subscales, and decreases on the Arousal subscale of the ERS. Gastroception may make distinct contributions to the benefits of body focus in a research context where the gut is often overlooked. Highlights: Sensing one's physiological processes may improve emotion regulation. This study measured interoception and regulation following gut and heart focus. Gut focus led to greater interoceptive sensibility and emotion regulation. The gut is often overlooked in interoception research, but may be a key location.